CO2 mitigation and carbon credit potential of traditional agroforestry at different elevations in Tehri district of North West Indian Himalaya - Vikrant, Kundan Kumar Vikrant; Dhanpal, Dr. D.S.Chauhan; Rizvi, Dr. R.H.Rizvi (Indian Journal of Agroforestry, 2025)
Agroforestry has sustainable attributes with both tangible and nontangible benefits. In this study carbon mitigation and credits potential of traditional agroforestry at different elevations were evaluated. These traditional agroforestry systems were: Agrihortisilviculture system (AHS), Agrihorticulture system (AH) and Agrisilviculture system (AS).Pant density, living biomass carbon and soil carbon were measured in each sample plot. Stem biomass was estimated by multiplying the stem volume with wood specific gravity using the maximum moisture content method. Branch and leaf biomass was estimated using the fresh and dry weight ratio. Walkley and Black method was used for estimating soil organic carbon percentage. Conversion factors were used for determination of Carbon stock and CO2 mitigation. Results show that Grewia oppositifoila was the predominant tree species occupying most of the agroforestry land use systems. Plant and soil organic carbon were significantly different (P ≤ 0.05) among systems and elevations, and varied with changing elevations and systems, Plant carbon was highest at lower elevations with AHS system, whereas, soil organic carbon was maximum at upper elevations with AH system. Total net carbon, including plant and soil, was significantly higher in the AH system at upper elevations. The total carbon credits and its value were higher at mid-elevations. The total value of C credits was calculated to be 2,036,489.13€ for agroforestry in Tehri District. It can be concluded that agroforestry has good potential for biodiversity conservation, CO2 mitigation and earning of carbon credit. Farmers can improve their livelihoods through carbon credits while concurrently protecting the environment.